Training on Making Herbal Drink to Increase Immunity in Pagelaran Village, Ciomas, Bogor - Tri Retno Handayani, Marybet; Yulianita; Wiendarlina, Ike Yulia; Utami, Novi Fajar; Mahyuni, Siti; Sulistiyono, Fitria Dewi; Komala, Oom; Hermawati, Ema; Rikkit (Jurnal Pengabdian Masyarakat Inovatif, 2023)
Health is a very valuable factor in life. One way to improve health or immunity is by consuming herbal drinks. Herbal drinks are believed to have beneficial properties for healing disease. Livelihoods in Pagelaran Village are dominated by laborers, farmers, traders and domestic workers, with educational levels dominated by junior high and high school levels. The problems found in Pagelaran Village are public health problems, so it is necessary to improve welfare, one of which is by consuming healty drinks made from herbal plants. Red ginger is widely used to treat various diseases such as colds, digestive disorders, antipyretic, anti-inflammatory and also analgesic. Compounds of lemongrass that have a good prospects for increasing immune system activity are usually flavonoids, curcumin, limonoids, vitamin C, vitamin E (tocopherol) and catechins. Lemons also contain quercetin which can increase the body's immunity. This PKM activitiy was carried out in Agroeduwisata Lembah Watu, Pagelaran Village, Bogor Regency, took the form of training in making herbal drinks to increase body’s immunity for women of PKK and KWT. The implementation of this PKM activity can increase the knowledge of utilizing, processing and packaging herbal plants into herbal drink products. This PKM activity, it is hoped that people will be able to make and consume health drinks which can be used to increase the body’s immunity so that the quality of life can improves too.